(untitled) (European Journal of Formal Sciences and Engineering, 2020)
The city of Tirana is subject to constant physical and spatial metamorphosis. In its urban territory, the different residential typologies are well distinguished by socio-economic conditions and the technical-constructive characteristics which have been influenced by political development of the country. The multi-family residential buildings from the post-war period up to the 1990s, in addition to the problems that accompanied them from their initial construction, are found today in front of a physical degradation derived from the years they have. Problematic residential spaces are also most of the buildings constructed in the first decade after 1990, characterized by a low technological and housing quality, derived from an uncontrolled and informal development of the building sector. The building quality in this research, is focused on the applied architectural standards, the technological solutions adopted and the energy consumption derived from them. From the analysis made it has been reached in the conclusions that a renewal and requalification process is necessary to reduce the energy waste and to increase the quality of housing within residential spaces. The main objective of this research is to contribute to the sustainable development of the residential area of Tirana, referring to both the architectural and technological scale. Sustainable development in this paper is closely linked to the quality of residential spaces, which is directly related to the quality of life of the inhabitants. Due to the complexity of the urban environment and its transformations over time, the identification of light regeneration and redevelopment strategies is fundamental, minimizing demolition works. This article includes numerous European examples and a theoretical part, from which proposals for the future development of the residential areas of the city of Tirana can be extrapolated.